The Prevalence and Impact of Mortality of the Acute Respiratory Distress Syndrome on Admissions of Patients With Ischemic Stroke in the United States. (November 2014) - Rincon, Fred; Maltenfort, Mitchell; Dey, Saugat; Ghosh, Sayantani; Vibbert, Matthew; Urtecho, Jaqueline; Jallo, Jack; Ratliff, John K.; McBride, John William; Bell, Rodney
Purpose: To determine the epidemiology of the acute respiratory distress syndrome (ARDS) and impact on in-hospital mortality in admissions of patients with acute ischemic stroke (AIS) in the United States. Methods: Retrospective cohort study of admissions with a diagnosis of AIS and ARDS from 1994 to 2008 identified through the Nationwide Inpatient Sample. Results: During the 15-year study period, we found 55 58 091 admissions of patients with AIS. The prevalence of ARDS in admissions of patients with AIS increased from 3% in 1994 to 4% in 2008 ( P < .001). The ARDS was more common among younger men, nonwhites, and associated with history of congestive heart failure, hypertension, chronic obstructive pulmonary disease, renal failure, chronic liver disease, systemic tissue plasminogen activator, craniotomy, angioplasty or stent, sepsis, and multiorgan failures. Mortality due to AIS and ARDS decreased from 8% in 1994 to 6% in 2008 ( P < .001) and 55% in 1994 to 45% in 2008 ( P < .001), respectively. The ARDS in AIS increased in-hospital mortality (odds ratio, 14; 95% confidence interval, 13.5-14.3). A significantly higher length of stay was seen in admissions of patients with AIS having ARDS. Conclusion: Our analysis demonstrates that ARDS is rare after AIS. Despite an overall significant reduction in mortality after AIS, ARDS carries a higher risk of death in this patient population.